Twelve protections evolved for the brain, and their roles in extending its functional life - Stone, Jonathan; Mitrofanis, John; Johnstone, Daniel M.; Robinson, Stephen R. (Frontiers in Neuroanatomy, 2023)
As human longevity has increased, we have come to understand the ability of the brain to function into advanced age, but also its vulnerability with age, apparent in the age-related dementias. Against that background of success and vulnerability, this essay reviews how the brain is protected by (by our count) 12 mechanisms, including: the cranium, a bony helmet; the hydraulic support given by the cerebrospinal fluid; the strategically located carotid body and sinus, which provide input to reflexes that protect the brain from blood-gas imbalance and extremes of blood pressure; the blood brain barrier, an essential sealing of cerebral vessels; the secretion of molecules such as haemopexin and (we argue) the peptide Aβ to detoxify haemoglobin, at sites of a bleed; autoregulation of the capillary bed, which stabilises metabolites in extracellular fluid; fuel storage in the brain, as glycogen; oxygen storage, in the haemoprotein neuroglobin; the generation of new neurones, in the adult, to replace cells lost; acquired resilience, the stress-induced strengthening of cell membranes and energy production found in all body tissues; and cognitive reserve, the ability of the brain to maintain function despite damage. Of these 12 protections, we identify 5 as unique to the brain, 3 as protections shared with all body tissues, and another 4 as protections shared with other tissues but specialised for the brain. These protections are a measure of the brain’s vulnerability, of its need for protection. They have evolved, we argue, to maintain cognitive function, the ability of the brain to function despite damage that accumulates during life. Several can be tools in the hands of the individual, and of the medical health professional, for the lifelong care of our brains.